2023
DOI: 10.3390/jcm12206461
|View full text |Cite
|
Sign up to set email alerts
|

Currently Debated Topics on Surgical Treatment of Pancreatic Ductal Adenocarcinoma: A Narrative Review on Surgical Treatment of Borderline Resectable, Locally Advanced, and Synchronous or Metachronous Oligometastatic Tumor

Sergio Pedrazzoli

Abstract: Background: Previously considered inoperable patients (borderline resectable, locally advanced, synchronous oligometastatic or metachronous pancreatic adenocarcinoma (PDAC)) are starting to become resectable thanks to advances in chemo/radiotherapy and the reduction in operative mortality. Methods: This narrative review presents a chosen literature selection, giving a picture of the current state of treatment of these patients. Results: Neoadjuvant therapy (NAT) is generally recognized as the treatment of choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 215 publications
0
1
0
Order By: Relevance
“…In the same study, patients with R1 duodenocephalic pancreatectomy (R1DP) showed significantly longer survival compared to patients who underwent a bypass surgical procedure ( 10 ). In a recent study by Pedrazzoli S. ( 11 ), it was concluded that the application of vascular resection in BRPHC carries an increased risk of complications and a higher mortality rate compared to standard PD.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, patients with R1 duodenocephalic pancreatectomy (R1DP) showed significantly longer survival compared to patients who underwent a bypass surgical procedure ( 10 ). In a recent study by Pedrazzoli S. ( 11 ), it was concluded that the application of vascular resection in BRPHC carries an increased risk of complications and a higher mortality rate compared to standard PD.…”
Section: Introductionmentioning
confidence: 99%